Scalable Dashboard for Identifying Split Failures and Heuristic for Reallocating Split Times. Issue 1 (2017) - Li, Howell; Richardson, Lucy M.; Day, Christopher M.; Howard, James; Bullock, Darcy M.
The three fundamental parameters of a traffic signal system are split, cycle, and offset. This paper describes the use of high-resolution data ( a ) to identify time periods during which split parameters may be insufficient and ( b ) to help practitioners identify opportunities for reallocating split time. A case study of seven corridors with 47 intersections is presented. A drill-down approach was developed to identify movements that could be improved by a reallocation of split times. A heuristic that can reallocate up to 5 seconds of underutilized green time on a competing phase was applied to those corridors. For the selected phase identified in this study, the adjustment reduced split failures by an average of 40% while also decreasing yellow occupancy an average of 40% and red light violations an average of 66%. The paper concludes by recommending that central systems implement drill-down dashboards. Such tools would enable easy identification and systemwide monitoring of split failures and would provide opportunities to reallocate slack time.